PENGARUH BUDAYA DAN SISTEM SOSIAL MASYARAKAT TERHADAP RUMAH SAKIT SEBAGAI INSTITUSI MEDIS: KAJIAN PUSTAKA TENTANG PENYESUAIAN HUKUM KESEHATAN UNTUK MENINGKATKAN PENERIMAAN LAYANAN KESEHATAN OLEH PASIEN - Hotmaria Hertawaty Sijabat; Gunawan Widjaja (CV. ADIBA AISHA AMIRA, 2025)
This study examines the influence of culture and social systems on hospitals as medical institutions and the importance of adjusting health laws to improve patient acceptance of health services. In a pluralistic society, cultural values and social structures are key factors that influence patients' perspectives, attitudes, and behaviour towards medical services. This literature review collects and analyses academic literature, legal regulations, and related case studies to identify the complex relationship between cultural, social, and health law aspects. The results of the study show that understanding and accommodating cultural diversity and social systems through inclusive and adaptive health law adjustments are essential to creating effective, humane medical services and increasing patient satisfaction and trust. This study provides recommendations for policymakers to develop health law regulations that are responsive to cultural and social diversity in order to support more equitable and equitable access to and quality of health services.